Influence of Nutrients on Growth, Fruitfulness and Leaf Nutrient Status of Olive (Olea europaea L.) - Kumar, Arun; Sharma, N. (International Journal of Bio-resource and Stress Management, 2023)
The anomalous and clogged uptake of nutrients and scrimpy soil fertility status were the main factors, which accounts for poor growth and yield of olive trees. Accordingly, olive trees of these areas exhibit a sublime response to foliar application of nutrients like nitrogen, potassium, boron and zinc in emboldening flowering and fruit set of olive. Keeping this in view, a field experiment was carried out during 2004-6 to infer the influence of nutrients on growth, fruitfulness and N, P and K, status in olive. The experiment consists of different treatments i.e. 0.5% Nitrogen (N), 0.5% Boric acid (H3BO3), 0.5% Zinc Sulphate (ZnSO4) and their amalgamations were given. Significantly higher shoot extension growth (6.09 cm) and leaf area (6.23 cm2) in olive, were observed in 0.5% N. Bloom intensity (0.58%) and fruit set (6.69%) were found significantly higher under 0.5% H3BO3+0.05% ZnSO4. Foliar application of 0.5% N has also culminated in a higher stomatal size (17.95×11.35 µm2), whereas a transcendent increase in stomatal density was recorded with control (79.84). Nitrogen content was perceived maximum under 0.5% N (1.72%), P(0.179%) and K (1.68%) content was found utmost under H3BO3 0.5%. The present investigation has evinced that application of 0.5% N was most efficacious in inducing optimum vegetative growth whereas, application of 0.5% H3BO3+0.5% ZnSO4 was most effectual in enhancing bloom intensity, perfect flowers and fruit set in olive. Foliar application of Boron and Zinc can aid in escalating foliar Zinc and Boron level in olive trees, which in turn plays their role in pollination, fertilisation and increased fruit set of olive trees.